Best Answer

6/13 - 4/12 =5/39

6/13 * 12/12 = 72/156

4/12 * 13/13 = 52/156

==============

....................20/156 or 5/39

Q: What does 6 13 - 4 12 equal to?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2

6 - 13 - 2 - 12 - 7 - 14 = -42

26/12 is equal to 13/6 in simplest form.

It's impossible for that to happen. 6 plus 7 is 13, not 12.

6/12 - 4/16 is equal to 1/2 - 1/4 and that is equal to 1/4

Related questions

13-12=1. Added to the original 1 = 2 10-4=6 6/2 (from the first line) = 3 !

2

1/3, 2/6, 3/9, 4/12

13

6 - 13 - 2 - 12 - 7 - 14 = -42

6+6=12 12-8=4

13 - 12 + 5 = 6

26/12 is equal to 13/6 in simplest form.

no 6 qt = 12 pt

4/12 - 6/12 = -2/12 or -1/6. Expressed as a decimal, this is equal to -0.16 recurring (that is, -0.16666...)

It's impossible for that to happen. 6 plus 7 is 13, not 12.

4x(4+sqrt(4))/sqrt(4) ======== 2nd Answer: The above would not equal 13. It would equal 12. 4*(4 + 41/2) / 41/2 = 4 * (4 + 2) / 2 = 4 * 6 / 2 = 12. However, if using powers is acceptable (such as square roots above) then a possible answer would be: 4 + 4 + 4 + 40 = 13